Optimal Pre-treatment and Resolubilization of Protease B from Bacillus licheniformis - Hossain*, Sk. Amir; Veide, Andres; Janson Kapca, Cecilia; Uhre, Kim Hanson; Jakobsen, Sune (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The study was designed to optimize physical parameters (e.g., temperature, maturation time and pH) related to protein solubility in order to reduce the cost of the total process of the enzyme production at industrial scale. We have studied the influence of physical parameters and chemical pre-treatment on the solubility of Protease B in detail. Protease B, a recombinant proteolytic enzyme produced from genetically engineered Bacillus licheniformis was used in this study. A longer protein solubility region as a function of pH and dry matter percentage was found at 4°C for Protease B. The maximum dry matter percentage was 20.1% RI (Refractive Index). The optimum protein solubility for Protease B solubility was found between 3.0 to 4.0 mS/cm conductivity within a pH range of 4.0 to 6.0. The solubility trend of the protein was not changed by the level of the enzyme concentration. This study clearly demonstrates that optimization of some physical parameters and chemical pre-treatment improves the solubility of Protease B and thus establishes the conditions of parameters in a cost-effective strategy of Protease B recovery and production at industrial scale. Keywords: Protein solubility, physical parameters, ultrafiltration concentrate, enzyme concentration, enzyme crystal. *Corresponding author: Mobile: +880-1720478775 E-mail: isti_99@yahoo.com.